Plant Growth Promoting Rhizobacter as an Alternative Liquid Organic Fertilizer Based on Bamboo Roots - Andi Ferina Herbourina Bonita; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Adji Syaifullah; Andi Ruum Syams Cakra (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Fulfillment of fertilizer is still a crucial problem for farmers, especially young farmers who depend on helping their parents in the fields or gardens because they have to stop going to school due to their parents' low economic conditions. The lack of skills in processing agricultural products and the natural environment means that when the harvest season is over, many youth members just hang out without working. The aim of implementing this service is to transform the potential of bamboo roots by encouraging out-of-school youth to contribute to helping other farmers regarding the limitations of fertilizer through fermentation techniques in producing Plant Growth Promoting Rhizobacter (PGPR) based on weathered bamboo roots for partners, namely the Out-of-School Youth Group. The implementation method for community service is a participatory approach to society that is implemented in three stages: socialization, training, and partner assistance. The results showed that partner members experienced a significant increase in their ability to understand the benefits of bamboo roots and convert them into biofertilizers, with an achievement of 90%. This activity helps the community, especially partners, obtain alternative fertilizers and companions to sustain agricultural products as the main commodity for the partners' parents' income.